Washington Street, ca. 1870 - Union Fire Society (Tufts Archival Research Center, 2005)
Elevated view south-southwest of Washington Street from Water Street. Signage and awnings adorn the facades of the buildings lining both the west-northwest and east-southeast sides of the street. Horse-drawn wagons and carriages fill the street, and pedestrians are visible along the sidewalks. The steeple of the Old South Meeting House, located at the northeast corner of Washington and Milk Streets, is visible along the east-southeast side of Washington Street. 3 1/8 x 2 15/16, 3 3/8 x 3 7/16 overall Stereographs